DIPLOMASI PENDIDIKAN SABAH BRIDGE DALAM MEMENUHI HAK PENDIDIKAN BAGI ANAK PEKERJA MIGRAN INDONESIA DI SABAH, MALAYSIA - Damayanti, Christy; Dewi, Untari Narulita Madyar; Permatasari, Defta Galuh (Indonesian Association for International Relations, 2023)
This research was conducted to describe the role of Sabah Bridge in conducting educational diplomacy in fulfilling the educational rights of Indonesian migrant workers' children through educational diplomacy. Qualitative research methods, literature studies, interview techniques, and educational diplomacy theory involving non-government actors were carried out. The results of the study show that there are three results from Sabah Bridge's educational diplomacy with related parties: (1) the Indonesian government built the Kota Kinabalu Indonesian school in Malaysia; (2) immigration cooperation between the two countries to facilitate documents needed by PMI children; and (3) Sabah Bridge and the Government of Indonesia provide repatriation scholarships to continue higher education in Indonesia. This research confirms that through diplomacy non-state actors can contribute to the national interests of their countries